Hepatitis G, hepatitis SEN, hepatitis TT and hepatitis TT-like viruses: New emerging hepatitis viruses in pediatric patients - Wiwanitkit, Viroj (Journal of Pediatric Infectious Diseases, 2006)
Hepatitis virus infection is an increasing problem with millions of affected cases all over the world. Recently, some new viruses have been identified for their association with hepatitis. These include hepatitis G, hepatitis SEN, hepatitis TT and hepatitis TT-like viruses. In this article, important information on epidemiology, pathogenicity, clinical manifestations, diagnosis and treatment of these viral infections are reviewed and presented.
Keywords: Viral hepatitis; new viruses; children